Impaired Pancreatic β-Cell Function in Critically Ill Children - Mohamed, Shereen A.; Badawi, Nora E.; AbdelRasol, Hoiyda A.; AbdelAziz, Hossam M.; Khalaf, Nirvana A.; Yousef, Remon M. (Frontiers in Pediatrics, 2021)
Critical illness hyperglycemia is common in the pediatric ICU. Increased glucose production, insulin resistance (IR) and pancreatic β-cell dysfunction are responsible mechanisms. We aimed to investigate β-cell function in the pediatric ICU and to uncover its relation to clinical and laboratory variables and ICU mortality. We prospectively recruited 91 children. Pancreatic β-cell function was assessed using homeostasis model assessment (HOMA)-β. Patients with β-cell function<40.0 % had significantly higher PRISM III scores, higher rates of a positive CRP, lower IR and a longer hospital stay. Those with 40-80% β-cell function had the highest IR. Intermediate IR was found when β-cell function was >80%. ICU survivors had better β-cell function than non-survivors. Multivariate logistic regression analysis revealed that higher PRISM III score and HOMA-β <80.0 % were significant predictors of mortality. In conclusion, β-cell dysfunction is prevalent in pediatric ICU patients and impacts on patient morbidity and mortality.